2019
DOI: 10.3390/agronomy9110690
|View full text |Cite
|
Sign up to set email alerts
|

Negative and Positive Impacts of Rape Straw Returning on the Roots Growth of Hybrid Rice in the Sichuan Basin Area

Abstract: Incorporating oilseed-rape straw in soil is one of the effective methods for enhancing the use efficiency of agricultural resources in the rape-rice rotation system. However, the impacts of oilseed-rape straw incorporation on root growth and dynamic changes in soil are still unclear. In order to provide a deeper understanding of the oilseed rape straw return on rice growth and productivity, the experiment was conducted in the field and in a specially-designed pots system from 2016 to 2017 by means of two straw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
1
15
0
1
Order By: Relevance
“…Straw is a comparatively abundant resources in China, producing 0.79 billion tons of straw annually (Zou et al., 2016). Considering from effective use of straw resources, more and more straw retuned into soil, especially in rape‐rice rotation system (Wang et al., 2019). Previous research has shown that the continuous introduction of oilseed‐rape straw into soil has created a better growth environment for rice yield by raising nitrogen, phosphorus, potassium (Yin, Zhao, Li, Cheng, & Liu, 2018), and soil organic matter content (Singh, Jalota, & Singh, 2007; Zhang, Hu, Li, Zheng, & Li, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Straw is a comparatively abundant resources in China, producing 0.79 billion tons of straw annually (Zou et al., 2016). Considering from effective use of straw resources, more and more straw retuned into soil, especially in rape‐rice rotation system (Wang et al., 2019). Previous research has shown that the continuous introduction of oilseed‐rape straw into soil has created a better growth environment for rice yield by raising nitrogen, phosphorus, potassium (Yin, Zhao, Li, Cheng, & Liu, 2018), and soil organic matter content (Singh, Jalota, & Singh, 2007; Zhang, Hu, Li, Zheng, & Li, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Lots of research reported positive impacts of straw incorporation on rice production in China, Asia and in the world wide, considering in a long period. With the development of harvest machine, more than 43.7% of the total rape straw in China has returned into soil (Wang et al., 2019), which cause the organic matter of rice field increased from 1.08% in 1990 to 2.56% in 2019 (Yin et al., 2018; Zhang et al., 2017). A 10 years study of the rice‐wheat rotation system in India showed a significantly increasing of phosphorus, potassium in soil, which caused the yield increase 4.6–10.4% of wheat and 3.8–10.2% of rice in straw returning treatment than straw burned treatment (Gupta, Ladha, Singh, Singh, & Pathak, 2007; Nandan et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations